1218. Genotypic Investigation of a Rotavirus Cluster at a Pediatric Hospital in 2022. (15th December 2022) - Yoon, Hee-won; Kitt, Eimear; Smith, Kenneth; Comar, Courtney E; Harris, Rebecca; Hopkins, Amy; Jaimes, Jose; Rustempasic, Slavica Mijatovic; Gautam, Rashi; Esona, Mathew D; Handy, Lori
Abstract: Background: Rotavirus group A (RVA) was the most common cause of infectious gastroenteritis among young children before introduction of rotavirus vaccine in the United States in 2006. Following widespread vaccination, U.S. hospital acquired (HA) rotavirus cases are rare. We describe a cluster of rotavirus infections in a pediatric hospital with a genotype uncommon among U.S. children. Methods: Patient cases of HA gastrointestinal (GI) illness were detected through hospital-wide microbiology surveillance, performed by Infection Prevention and Control (IPC) practitioners per state requirements. Cluster procedures were implemented on a unit when 3 cases were identified by symptoms and/or laboratory tests within 48 hours. Due to the current rarity of rotavirus clusters, the hospital partnered with Centers for Disease Control and Prevention (CDC) laboratories to sequence strains in addition to instituting local control measures. RVA strains were genotyped by using the genotype specific qRT-PCR assays for VP7 and VP4 genes. Next Generation Sequencing (NGS) was performed for RVA strain characterization on Illumina MiSeq. Genotypes for all 10 RVA were determined by NCBI's BLASTN program. Results: Epidemiologic surveillance identified a rotavirus cluster of 10 patients aged 10 months to 10 years old, of whom 50% had received rotavirus vaccine. Symptoms included emesis and diarrhea. Cases could not be attributed to vaccine related shedding. All patients had epidemiologic links by contiguous bed spaces or shared care teams. Sequencing was conclusive for 9 of the 10 stool samples to be a G9P[4] genotype, which is rarely detected amongst U.S. children. Local control measures of increased education and cleaning, isolation of positive patients in single rooms, use of soap and water instead of alcohol-based hand sanitizer on room exit, and furlough of symptomatic healthcare workers halted transmission. Conclusion: Routine surveillance of HA GI illness identified a cluster; RVA strain genotyping and characterization identified unusual rotavirus genotype G9P[4] as the cause. Partnership between IPC practitioners and laboratorians with CDC demonstrated the need to enhance infection prevention measures to halt transmission and identified a rare rotavirus strain as the likely cause of the cluster. Disclosures: Courtney E. Comar, PhD, Pfizer: Stocks/Bonds|Viatris: Stocks/Bonds.